Treating Pb-contaminated clay slurry by three curing agents - Li, Wentao (2022)
Each year, extensive dredged clay slurries containing heavy metals need to be treated before being reused; in such contaminated slurries, lead (Pb) is frequently identified. Quicklime (CaO)-activated ground granulated blast-furnace slag (GGBS), magnesium (MgO)-activated GGBS, and ordinary Portland cement (OPC) are usually used to remediate the lead (Pb)-contaminated soil; nevertheless, using these curing agents (or binders), particularly CaO-GGBS and MgO-GGBS, to treat Pb-contaminated slurry with high water content is rarely reported. Moreover, inconsistent results were obtained from previous studies in terms of the mechanical and leaching performance of Pb-contaminated soils with the three binders. Based on the above-mentioned reasons, this study used CaO-GGBS, MgO-GGBS, and OPC to treat the Pb-contaminated clay slurry, and compared the effectiveness of the three binders in improving the mechanical and leaching properties of the slurry. Laboratory tests were performed to examine the leaching, strength, mineralogical, and micro-structural performance of treated clay slurries. The results showed that GGBS-based binders were more effective than OPC in improving the strength and Pb leachability of contaminated slurries. When suitable ratios between activators (CaO and MgO) and GGBS were used, a similar or even higher UCS was produced by CaO-GGBS than MgO-GGBS. Similar leachate pH and Pb leachability could be achieved between CaO-GGBS- and MgO-GGBS-treated contaminated clay slurries. Therefore, it is not rigorous to state that MgO-GGBS is better in improving the strength and leachability of Pb-contaminated soils than CaO-GGBS only by comparing the two GGBS-binders based on the same activator/GGBS ratio, as reported in some previous studies. The leachability of Pb was affected by the pH, but the addition of GGBS facilitated the decrease of Pb leachability in slurries. The XRD result showed the formation of CSH and Pb(OH)2, which facilitated the reduction of Pb leachability.